2022
DOI: 10.1007/s11096-022-01523-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with prescription drug monitoring program utilisation: a cross-sectional survey of community pharmacists

Abstract: Background Prescription drug monitoring programs (PDMP) are databases which collect prescribing and dispensing information for high-risk medicines, and are one approach to mitigate prescription opioid-related risks. Aim To examine correlates of PDMP use under voluntary and mandatory conditions, among a representative sample of community pharmacists in Victoria, Australia. Method An online anonymous survey was conducted and collected data in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Data were collected as part of a larger study examining the implementation of Victoria's Prescription Drug Monitoring Program [24,25]. A representative sample of Victorian community pharmacists was invited to anonymously participate in an online cross-sectional survey.…”
Section: Design and Settingmentioning
confidence: 99%
“…Data were collected as part of a larger study examining the implementation of Victoria's Prescription Drug Monitoring Program [24,25]. A representative sample of Victorian community pharmacists was invited to anonymously participate in an online cross-sectional survey.…”
Section: Design and Settingmentioning
confidence: 99%
“…Zhang et al [25] reported that Western Australian pharmacists who were future PDMP users were comfortable with mandated use. Amongst a sample of Victorian pharmacists, Picco et al [12] reported that 24.9% used the PDMP all of the time under voluntary conditions, compared with 51.7% once mandated. Prathivadi et al [11] revealed that Victorian general practitioners reported higher use of the mandatory PDMP compared with practitioners in other states.…”
Section: Optimising Pdmp Information and Data Access Including Practi...mentioning
confidence: 99%
“…PDMPs are now widely adopted tools designed to facilitate safer clinical decisions and reduce patient harm, however, practitioner use may be suboptimal [3,6,[9][10][11][12][13]. Successful achievement of PDMP objectives relies on effective and optimal PDMP use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation